Caracterização genética de rinovírus humano em amostras de populações distintas do Estado de São Paulo - Watanabe, Aripuanã Sakurada Aranha [UNIFESP] (2012)
Infections caused by Human Rhinoviruses (HRVs) account for 25%-50% of respiratory illnesses among individuals presenting influenza-like illness (ILI). HRVs could be classified in at least three species: HRV-A, HRV-B, and HRV-C. The HRV-C species has frequently been described among children and apparently has led to severe illness resulting in hospitalization; however, the occurrence among adults is unknown. The aim of this study was to assess the clinical presentation and species distribution of HRV infections in different populations during 2001-2005. A total of 682 samples were collected. Subjects consisted of 132 adults from the general community and 198 health-care workers (2001-2003), 242 renaltransplanted outpatients (2002-2004), 61 children with congenital heart disease (2005) and 49 elderly persons from Botucatu city, Sao Paulo, Brazil (2003-2004). Amplification of HRV genes was performed by Reverse Transcriptase – Polymerase Chain Reaction (RT-PCR) and followed by sequencing and phylogenetic analysis. HRV was detected in 24.05% of samples (164/682), 15.2% (20/132) among adults from general community, 29.8% (59/198) among health-care workers, 23.6% (57/242) among renal-transplanted outpatients, 22.9% (14/61) among children with congenital heart disease and 28.6% (14/49) among elderlies. A total of 85.5% (137/164) previously positive HRV samples were sequenced and 79.9% (131/164) were analyzed. We identified 80 isolates (61.0%) of the HRV A species, 22 (16.8%) of the HRV B species and 29 isolates (22.2%) of the HRV C species. High ILI rate (38.9%) was found among HRV infected patients. Logistic regression showed a three-fold increase in prevalence of ILI in individuals with HRV A infection compared with HRV C infected patients. HRV infections caused ILI among non-hospitalized patients. HRV specie A was associated with a disease more intense than a common cold. The dynamics of infection among different species deserve further analysis.